2019
DOI: 10.33394/jollt.v7i2.1958
|View full text |Cite
|
Sign up to set email alerts
|

Practicing Discussion in the Form of Pyramid to Improve Students’ Speaking Performance and Classroom Interaction

Abstract: Speaking is an ability to use the language in oral form to express what is on language learners’ thinking. Learners have speaking skills if they have skills to practice grammar, comprehension, vocabulary, pronunciation, and fluency in the oral form. To attain the speaking skills, English teachers are encouraged to meet an appropriate learning strategy to be applied in the speaking classes. This study is a collaborative classroom action research. It is aimed at describing how the use of pyramid discussion to en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 4 publications
1
14
0
Order By: Relevance
“…On the other hand, when the students are having talks with other students, the situation is not that terrible. This finding is in accordance with Buhari (2019) who finds that the interaction between students with a classmate is seen interactively rather than with their teachers. Besides, Bohari (2019) argues that peer-talk provides learners more open-minded in learning rather than teacher-students conversation.…”
Section: Research Findings and Discussion Research Findingssupporting
confidence: 92%
“…On the other hand, when the students are having talks with other students, the situation is not that terrible. This finding is in accordance with Buhari (2019) who finds that the interaction between students with a classmate is seen interactively rather than with their teachers. Besides, Bohari (2019) argues that peer-talk provides learners more open-minded in learning rather than teacher-students conversation.…”
Section: Research Findings and Discussion Research Findingssupporting
confidence: 92%
“…Horwitz and Cope (1986: 13-14) identified three components of foreign language anxiety: 1) Communication apprehension is a type of shyness characterized by a fear of anxiety about communicating with people; 2) Test anxiety refers to a type of performance anxiety stemming from a fear of failure. It was reinforced by Buhari, (2019) who found that fear of failure influences students' speaking competences. Students with test anxiety often demand more of themselves than they are capable of achieving and worry about their performance; 3) Fear of negative evaluation involves apprehension about others' evaluation, avoidance of evaluative situation and the exception that they would evaluate oneself negatively.…”
Section: Introductionmentioning
confidence: 99%
“…An observation towards students of grade eight at SMPN 4 Praya led the researcher to find that students had the struggle to master vocabulary, especially spotted during the writing activity. For instance, the students who were lack of vocabulary seemed problematic in determining the meaning of words (Buhari, 2019). Moreover, they demonstrated difficulty in differentiating the form of speech, not knowing how to express an idea in written form, and tend to be passive participants in the classroom.…”
Section: Introductionmentioning
confidence: 99%